Optimizing use of wet sorghum distiller’s grains with solubles in flaked-corn finishing diets - Daubert, R.W.; Loe, E.R.; Sindt, J.J.; Fox, J.T.; Greenquist, M.A.; Corrigan, M.E.; Drouillard, James S.; Depenbusch, Brandon E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A finishing trial was conducted using 637 heifers (initially 849 lb) to determine the optimal amount of wet sorghum distiller's grains with solubles (WDGS) in finishing diets containing steam-flaked corn. Dietary treatments consisted of six concentrations of WDGS (0, 8, 16, 24, 32, and 40%; dry basis). Heifers were placed into dirt-surfaced feedlot pens (25 to 30 heifers/pen; 4 pens/treatment) and fed for 58 days. Daily gain responded in a quadratic manner (P<0.01), peaking with 8% WDGS in the finishing diet. Average daily gains during the 58-day finishing period were 2.79, 3.11, 3.05, 2.89, 2.70, and 2.55 lb/day for cattle fed 0, 8, 16, 24, 32, and 40% WDGS, respectively. Dry matter intake decreased linearly (P<0.01) as content of WDGS increased. Feed efficiency was optimized with 16% WDGS (6.81, 6.49, 6.19, 6.64, 6.96, and 7.18 lb dry feed per lb gain for cattle fed 0, 8, 16, 24, 32, and 40% WDGS, respectively). Animal performance data were used to compute net energy gain (NEg) values of each diet, yielding estimates of 69.9, 71.7, 75.8, 71.2, 68.9, and 67.6 Mcal/cwt for diets containing 0, 8, 16, 24, 32, and 40% WDGS, respectively (quadratic effect, P<0.03). Ribeye area decreased linearly (P<0.02) as concentration of WDGS increased in the diet. The percentage of USDA Yield Grade 1 carcasses decreased linearly (P<0.05), and the percentage of USDA Yield Grade 3 carcasses increased linearly (P=0.05) as the content of WDGS was increased. Average USDA Yield Grade increased linearly (P<0.02) as content of WDGS was increased. Grid-based carcass values were not significantly different across dietary treatments. Regression analysis of efficiency data indicates that the optimum amount of sorghum WDGS in steam-flaked corn diets is approximately 15%. Diets containing as much as 24% WDGS yielded efficiencies equal or superior to diets containing no WDGS.
Keywords: Beef; Wet sorghum; Distillers grains; Flaked-corn